Analysis of online sales distribution channels in international companies in south america and their profitability and competitiveness - Salvador De Souza, Andrés (2018)
Over time, the Internet has changed the way people communicate, and not only that, but also how they make different transactions to acquire goods, transfer money, and entertain themselves. In this matter, distribution channels play a substantial role on strategies companies develop so as to revolutionize how business is made. With the application of informatics tools and the use of Internet and technology, companies can implement online channels that will make them gain competitive advantage and increase profitability. These new digital channels such as web pages, mobile apps, and social networks will help companies to interact directly with their customers, bringing the opportunity of reducing costs, improving their brand reputation, and reaching wider audiences. Moreover, it is important to mention that customers became main actors with the evolution of web 2.0, so it is imperative to comprehend how human behavior works and how companies can develop strategies around it. In this sense, this dissertation project aims to analyze the South American context regarding the development and implementation of online sales distribution channels, as well as the relation with the region’s potential and the impact on companies and their customers. In order to achieve this, Web 2.0 Theory, E-commerce, Distribution Channels as part of a Marketing Theory and Consumer Behavior are used as the theoretical framework, and the selected methodology is based on descriptive and exploratory premises to analyze theoretical concepts and relate them to empirical data from a real case.